A causal model to explore the ACAS induced collisions. (August 2014) - Jun, Tang; Piera, Miquel Angel; Ruiz, Sergio
Current Air Traffic Management research programs (i.e. Single European Sky ATM (air traffic management) Research (SESAR), next generation air transportation system (NextGen)), try to overcome airside capacity shortages while improving cost-efficient operations and safety. An increment in the airspace traffic density can lead to congested traffic scenarios for which it becomes necessary to develop new safety procedures that address multithread threats. This paper considers some of the difficulties in establishing validation of the airborne collision avoidance system (ACAS), which constitutes the last-resort for reducing the risk of near mid-air collision between aircraft in a multithread scenario. A causal model that is specified in Colored Petri Net (CPN) formalism is presented as a key approach to analyze the state space of a congested traffic scenario in which the events that could transform a conflict into a collision are identified, providing a challenging tool not only for validation but also for the implementation of a new ACAS logic. The InCAS EuroControl simulator has been used to illustrate the importance of cause–effect analysis for the relationships between various encounters that arise in a multithread scenario, in which TCAS II v. 7.1 fails to avoid a collision when two Resolution Advisories are issued without consideration of the downstream effects.